The changing character of democracy in the pre and post colonial Cameroon: An old practice, a new word - LINDA ANKIAMBOM LAWYER (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This article aims to chart the development of democracy in Cameroon over various historical periods. Since the dawn of time, democracy has been practiced worldwide. Because of this, whether you’re talking about Athenian democracy or the democracy in the United States, both have their roots in the past. This was the case with the African and Cameroonian democracies, which predated colonialism.Methodology: Data is collected using an interdisciplinary strategy, and the past is analyzed using a functional framework.Findings: The data gathered using historical research methods led to the conclusion that democracy is a work in progress and not a perfect system. Cameroonians can incorporate new democratic norms into their country’s established system. Customs.Novelty/Implications: The results of this study demonstrate that the Cameroonian culture before colonization was governed fairly well. Both historical and modern Cameroonian societies were inclined to pursue some form of social progress. It is analyzed, and recommendations are made for Cameroonian and African societies.